Uganda : post-conflict reconstruction : country case evaluation - Kreimer, Alcira; World Bank. (Washington, D.C. : World Bank, 2000)
This case study assesses the World Bank's experience in assisting post-conflict reconstruction in Uganda.
At head of title: World Bank Operations Evaluation Department, OED.
Includes bibliographical references (p. 79-80).
osc 26/8/16
Loans
Keywords: Economic assistance - Uganda; World bank - Uganda; Uganda - economic conditions; Uganda